2007
DOI: 10.1071/mf06236
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of near-surface chlorophyll a in the Great Barrier Reef lagoon

Abstract: Surface chlorophyll a concentrations in the Great Barrier Reef (GBR) lagoon were monitored at individual stations for periods of 6 to 12 years. The monitoring program was established to detect spatial and temporal changes in water quality resulting from increased loads of nutrients exported from the catchments adjoining the GBR. Sampling occurred monthly at up to 86 sites that were located in transects across the width of the continental shelf. In the central and southern GBR (16–21°S), there was a persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 34 publications
10
106
1
Order By: Relevance
“…Coastal waters adjacent to agricultural lands have higher concentrations of dissolved and particulate nutrients, chlorophyll a and suspended sediments, especially during the summer wet season, compared to coastal areas adjacent to undeveloped catchments and offshore areas (e.g., Brodie et al 2007;Cooper et al 2007). However, water quality parameters are highly variable in space and time which necessitates frequent measurements to adequately determine true concentration ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal waters adjacent to agricultural lands have higher concentrations of dissolved and particulate nutrients, chlorophyll a and suspended sediments, especially during the summer wet season, compared to coastal areas adjacent to undeveloped catchments and offshore areas (e.g., Brodie et al 2007;Cooper et al 2007). However, water quality parameters are highly variable in space and time which necessitates frequent measurements to adequately determine true concentration ranges.…”
Section: Introductionmentioning
confidence: 99%
“…However, these relationships were generally from temperate areas and few measurements were included from tropical river catchments. The nutrient run-off issue is of particular concern for tropical river catchments adjacent to the Great Barrier Reef (GBR) because of possible downstream impacts of additional nutrients on this coral reef ecosystem (Fabricius 2005;DeVantier et al 2006;Brodie et al 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…The downstream impacts of this run-off into GBR waters are of major concern; however, the direct effects of agricultural run-off on reef communities have been difficult to measure and are, as a result, controversial. Recent research DeVantier et al 2006) has shown a decline in hard-coral richness within the latitudinal zone of 14-18 • S, together with an increase in chlorophyll a concentrations in the central inshore GBR lagoon (Brodie et al 2007a). This zone of apparent change lies adjacent to coastal catchments with high levels of fertiliser-additive land use (FALU), mostly sugarcane, which is relatively close to the GBR.…”
Section: Introductionmentioning
confidence: 99%
“…Chl-a concentrations in the waters off Cape York average 0.2 µg L −1 , whereas in the area of coral reef biodiversity loss (wet tropics coast) concentrations average 0.7 µg L −1 . The difference is ascribed to the increased nutrient discharge from rivers such as the Tully caused by increased erosion and fertiliser loss (Mitchell et al 2001(Mitchell et al , 2009Furnas 2003;McKergow et al 2005a;Brodie et al 2007). Water quality trigger values for the GBRWHA have been set for chl-a at 0.6 µg L −1 for inshore waters (Moss et al 2005) and later to 0.5 µg L −1 (GBRMPA 2008; since then reduced to 0.45 µg L −1 ), and this value (0.5 µg L −1 ) was used as the GBR target for the Tully WQIP.…”
Section: Target Setting For the Tully-murray Basin For Nitratementioning
confidence: 99%